Study of Electrical Properties of Modified Polypyrrole Composites Synthesized Using Different Concentrations Ce3+ Rare Earth Metal Salt as Dopant (International Journal of Scientific Research in Science and Technology, 2024)
In the present research workPPy/CeCl3 composites were synthesized by using simple oxidative polymerization method by using ammonium peroxydisulphate as an oxidizing agent with simultaneous doping during the synthesis at 0.01 M and 0.2 M concentrations of dopant CeCl3. Structural, Morphological, and Thermal characterization of synthesized composites was carried out by IR, NMR, Mass, SEM, XRD, TGA and DTA studies. The Electrical properties of synthesized composites were studied by using four probe methods. FTIR, Mass and NMR studies , provides insights about the chemical composition of the composite. Morphological studies employing scanning electron microscopy (SEM) and X-ray diffraction, reveals the crystallinity, surface morphology, particle size distribution and interfacial characteristics of the synthesized composite. Thermal properties are investigated using TGA and DTA analysis, shedding light on its thermal stability, degradation behavior, and the impact of CeCl3 incorporation on these properties. the electrical conductivity of the composite is examined using a four-point probe technique, demonstrating the influence of CeCl3 on the electrical performance of the PPY matrix. The results suggest potential applications for the PPY/CeCl3 composites in advanced materials and electronic device fields such as sensors, actuators, and energy storage devices.